2008
DOI: 10.1161/hypertensionaha.107.189010
|View full text |Cite
|
Sign up to set email alerts
|

Call to Action on Use and Reimbursement for Home Blood Pressure Monitoring

Abstract: Abstract-Home blood pressure monitoring (HBPM) overcomes many of the limitations of traditional office blood pressure (BP) measurement and is both cheaper and easier to perform than ambulatory BP monitoring. Monitors that use the oscillometric method are currently available that are accurate, reliable, easy to use, and relatively inexpensive. An increasing number of patients are using them regularly to check their BP at home, but although this has been endorsed by national and international guidelines, detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
237
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 487 publications
(249 citation statements)
references
References 181 publications
(169 reference statements)
3
237
0
9
Order By: Relevance
“…14 Cuspidi et al 15 conducted a multicenter survey in Italy and found that 640 (75%) of 855 hypertensive patients had been regularly performing home BP measurements. Almost all hypertensive patients in the United States and Japan have a home sphygmomanometer 4,16,17 and 90-95% of the physicians recommend HBPM in Japan. 17 Because of lower income level and educational status, the lower rate of ownership of home sphygmomanometers in Turkey, a developing country, compared with developed countries, was not surprising.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…14 Cuspidi et al 15 conducted a multicenter survey in Italy and found that 640 (75%) of 855 hypertensive patients had been regularly performing home BP measurements. Almost all hypertensive patients in the United States and Japan have a home sphygmomanometer 4,16,17 and 90-95% of the physicians recommend HBPM in Japan. 17 Because of lower income level and educational status, the lower rate of ownership of home sphygmomanometers in Turkey, a developing country, compared with developed countries, was not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Incorrect recording of readings and inappropriate cuff size are two factors affecting the reliability of HBPM. 4 The feature of memory associated with the devices is quite useful and therefore is recommended. [2][3][4] Bringing the device to the physician, when visiting, serves to reduce problems due to inaccurate recording of readings and increases the reliability of HBPM, but only a limited number of patients were performing this, according to our survey.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations